Microstrip Patch Antenna Bandwidth Enhancement Using AMC/EBG Structures - R. C. Hadarig; M. E. de Cos; F. Las-Heras (International Journal of Antennas and Propagation)
A microstrip patch antenna with bandwidth enhancement by means of artificial magnetic conductor (AMC)/electromagnetic band-gap structure (EGB) is presented. The electrical characteristics of the embedded structure are evaluated using MoM simulations. The manufactured prototypes are characterized in terms of return loss, gain, and radiation pattern measurements in an anechoic chamber.